Identification of bioactive compounds of Bacillus velezensis HNA3 that contribute to its dual effects as plant growth promoter and biocontrol against post-harvested fungi - Zaid, Doaa S.; Li, Wenya; Yang, Siyu; Li, Youguo (Microbiology spectrum, 2023)
Bacillus velezensis HNA3 displayed dual bioactivities as a plant growth promoter and a biocontrol agent against five isolated post-harvest phytopathogens: Alternaria alternata , Cladosporium cladosporioides , Penicillium expansum , Monilinia fructicola , and Fusarium oxysporum . Moreover, the volatile organic compounds (VOCs) emitted by HNA3 exhibited remarkable efficacy, achieving 100% fungal inhibition against Alternaria alternata and Cladosporium cladosporioides . This is the initial study to demonstrate the HNA3-emitted VOCs effect on enhancing soybean seedling growth and seed germination by breaking seed dormancy and improving root construction. Semi-VOCs and emitted VOCs were identified by two methods of extraction coupled with gas chromatography-mass spectrometry. A total of 14 main VOCs were detected; phenol,2,4-bis(1,1-dimethylethyl) and 1,2-benzenedicarboxylic acid are the most abundant semi-VOCs, both are known to have anti-fungal and plant growth-promoting properties. 9-Octadecenoic acid (z)-, methyl ester is the most common volatile compound emitted by HNA3 followed by hexadecanoic acid, methyl ester and heptadecanoic acid, methyl ester. It is noteworthy that heptadecanoic acid, methyl ester has not been previously detected in Bacillus spp. Pure 9-octadecenoic acid (z)-, methyl ester, as well as heptadecanoic acid, methyl ester, exhibited inhibitory effects on the fungal growth of all isolated phytopathogens. Interestingly, when combined, these compounds synergistically eradicated fungal growth. Indole acetic acid and serotonin, both classified as plant growth-promoting indoles, have been identified within HNA3. Moreover, during the phytopathogen inhibition stage, HNA3 demonstrated upregulation in gene expression associated with non-VOCs, including bacillibactin, bacillomycin, bacilysin, and surfactin. This study publicized an extensive variety of bioactive compounds produced by HNA3 liable for its bioactivities. The current study is an extension to our previous work on the plant growth-promoting rhizobacteria (PGPR) Bacillus velezensis HNA3 strain, which comes to confirm and reveals the huge stock of active secondary metabolites produced by HNA3. HNA3-emitted volatile organic compounds (VOCs) have demonstrated the capacity to impede the growth of phytopathogens affecting some fruits and vegetables, even in the absence of direct contact. Additionally, these volatiles enhanced soybean seed germination by breaking seed dormancy and inducing root system development. Furthermore, they promoted seedling growth, giving it prominence in soybean cultivation. The relevance of active volatiles derives from the fact that they can be developed as natural-safe biocontrol agents and plant promoters. This research validates the remarkable bioactivities exhibited by the Bacillus velezensis HNA3 and their potential applications in agriculture as an inoculant, encompassing biocontrol, plant growth promotion, and seed germination activities, thereby offering a safer alternative to hazardous chemicals.